Antimicrobial Susceptibility and Genetic Characterisation of Burkholderia pseudomallei Isolated from Malaysian Patients. (14th October 2014) - Khosravi, Yalda; Vellasamy, Kumutha Malar; Mariappan, Vanitha; Ng, Shet-Lee; Vadivelu, Jamuna
Abstract : Burkholderia pseudomallei, the causative agent of melioidosis, is intrinsically resistant to many antibiotics. Ceftazidime (CAZ), the synthetic β -lactam, is normally used as the first-line antibiotic therapy for treatment of melioidosis. However, acquired CAZ resistance can develop in vivo during treatment with CAZ, leading to mortality if therapy is not switched to a different antibiotic(s) in a timely manner. In this study, susceptibilities of 81 B. pseudomallei isolates to nine different antimicrobial agents were determined using the disk diffusion method, broth microdilution test and Etest. Highest percentage of susceptibility was demonstrated to CAZ, amoxicillin/clavulanic acid, meropenem, imipenem, and trimethoprim/sulfamethoxazole. Although these drugs demonstrated the highest percentage of susceptibility in B. pseudomallei, the overall results underline the importance of the emergence of resistance in this organism. PCR results showed that, of the 81 B. pseudomallei, six multidrug resistant (MDR) isolates carried bpeB, amrB, and BPSS1119 and penA genes. Genotyping of the isolates using random amplified polymorphic DNA analysis showed six different PCR fingerprinting patterns generated from the six MDR isolates clusters (A) and eight PCR fingerprinting patterns generated for the remaining 75 non-MDR isolates clusters (B).